Enhancing Supply Chain Efficiency and Green Logistics: The Role of Environmental Regulations - Abdulrahman Al-Kharabsheh; Nasser Assaf; Lana Barakat Salman Al-Shoura; Hashem Osamah Yahya Mohammed; Baker Akram Falah Jarah (Brighteredge Press Resources, 2026)
Indexed by ( Tier 2)